Ameliorative Effects of Dietary Ellagic Acid Against Severe Malaria Pathogenesis by Reducing Cytokine Storms and Oxidative Stress - Mohanty, Shilpa; Gupta, Amit Chand; Maurya, Anil Kumar; Shanker, Karuna; Pal, Anirban; Bawankule, Dnyaneshwar Umrao (Frontiers in Pharmacology, 2021)
Ellagic acid (EA), a fruit- and vegetable-derived flavonoid, has been reported for multiple pharmacological activities, which encouraged us to examine its useful effect in severe malaria pathogenesis, especially malaria-induced cytokine storms and oxidative stress linked to damage in major organs. Malaria was induced by injecting Plasmodium berghei–infected RBCs intraperitoneally into the mice. EA was given orally (5, 10, and 20 mg/kg) following Peter’s 4-day suppression test. EA exhibited the suppression of parasitemia, production of inflammatory cytokine storms and oxidative stress marker level quantified from vital organs significantly and an increase in hemoglobin, blood glucose, and mean survival time compared to the vehicle-treated infected group. EA administration also restored the blood–brain barrier integrity evidenced through Evans blue staining. Furthermore, we demonstrated the protecting effect of EA in LPS-induced inflammatory cytokine storms and oxidative stress in glial cells. The present study conclude that ellagic acid is able to alleviate severe malaria pathogenesis by reducing cytokine storms and oxidative stress–induced by malarial parasites. It also attributed promising antimalarial activity and afforded to improve the blood glucose and hemoglobin levels in treated mice. These research findings suggested the suitability of ellagic acid as a useful bioflavonoid for further study for the management of severe malaria pathogenesis.